Resistensi Wereng Batang Cokelat Padi, Nilaparvata lugens Stål terhadap Insektisida di Indonesia - Sutrisno Sutrisno (Balai Besar Penelitian dan Pengembangan Bioteknologi dan Sumber Daya Genetik Pertanian, 2014)
The ricebrown planthopper (BPH), Nilaparvata lugens (Stål) is amajor insect pest of rice and their infestations occur everyyear in several locations in Indonesia. The use ofinsecticides often fails to control the BPH so theirpopulations are still high that cause rice crops showhopperburn and the farmer loses the yields. Thedevelopment of insecticide resistant in BPH population isone of the factors to contribute to the failure of insecticidescontrol. We have detected the development of fieldpopulation BPH resistance to BPMC, carbofuran, MIPC, andimidacloprid, but we do not know yet the development ofresistance to other insecticides to control BPH in Indonesia.This paper will review several cases on BPH resistance toinsecticides in Indonesia and other countries that includeaspects of the development of resistance in the field and inthe laboratory, the mechanism of resistance, inheritance ofresistance, genomics of resistance, and resistancemanagement. A policy and further study is also suggested forinsecticide resistance management in Indonesia.